CONSTRUCTIONISM AS A MEDIA PARADIGM - Marković, Branko (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2018)
Research of the nature of mass communication by using different theoretical approaches has gone a long way since its perception as a transmission of symbolic content (whose aim is to create certain effect used for confirming or questioning social order) to the construction of symbolic or media reality. The media simultaneously create reality through symbolic legitimization, which does not eliminate the possibility of their planned impact on the audience. In this case, the intentionality of the media appears as long-term product of their significant role with a completely uncertain outcome. Namely, interpretative frameworks whose bearers are social institutions, organizations, interest groups, political parties and individuals create numerous definitions of reality reproduced by symbolic activity of the media in the processes of legitimization and delegitimization. In these terms, according to Hall, the media are secondary definers, whereas the leading social institutions and organizations are primary definers of reality (Hall, 1978:57). The confrontation between different definitions of reality always actualizes the issue of power, as well as the media conditions in which they are implemented. Thus, mass media appear as an infrastructure for the objectivization of different presentations through the process of creating symbolic construction. Aside from constructing reality, the media are part of that reality as well. Perceiving media reality as the result of specific form of management and production of meaning is a shift in the perception of the media in society. The mass media practice is thus not observed from the aspect of message transfer, but as a process of producing meaning in marking reality. In this way, media contents offer reference and interpretative frameworks for interpreting actual events and in some cases, they replace them.